Implementation of Schoology, Zoom, and Faststone as an Effort to Optimize Participation in Evaluation Course: Pandemic Solution - Rahmawati, Laili Etika; Purnanto, Arif Wiyat; Kurniawan, Andra (Prosiding University Research Colloquium, 2023)
This study aims to optimize student active participation in learning the Indonesian Language Learning Evaluation course during the Corona lockdown by implementing several learning media, namely Schoology, Zoom, and Faststone. This study applies a classroom action research method. The object of this research is students taking the Indonesian Language Learning Evaluation course in the Indonesian Language and Literature Education study program, FKIP, Muhammadiyah University of Surakarta which consists of 207 students who are divided into 5 classes, namely A, B, C, D, and E with each of them. The number of students in each class is 45 for classes A, B, C, and D, and 27 students for class E. The results of the study in cycle 1 show that the level of student participation in classes A, B, C, D, and E is 84%, 82 %, 56%, 64% and 93%. Cycle 2 shows an increase in the participation rate of students in classes A, B, C, D, and E, respectively, 91%, 80%, 82%, 84%, and 59%. Cycle 3 shows that the participation rate of students in classes A, B, C, D, and E has changed, namely 84%, 100%, 76%, 95%, and 67%.